2021
DOI: 10.1523/jneurosci.1074-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Inner Hemispheric and Interhemispheric Connectivity Balance in the Human Brain

Abstract: The connectome of the brain has a great impact on the function of the brain as the structure of the connectome affects the speed and efficiency of information transfer. As a highly energy-consuming organ, an efficient network structure is essential. A previous study has shown consistent overall brain connectivity across a large variety of species. This connectivity conservation was explained by a balance between interhemispheric and intrahemispheric connections; that is, spices with highly connected hemisphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…While many anatomical tracing studies focus only on ipsilateral connections within a hemisphere, PMv has many transcallosal connections with heterotopic areas in the other hemisphere 67 , 68 and consistent with this anatomical observation it is established that PMv exerts similar facilitatory and inhibitory influences over the activity of M1 both ipsilaterally and contralaterally 45 , 46 , 66 , 69 , 70 . Therefore, the PMv-to-M1 circuit can also be studied interhemispherically, thus making it possible to probe mechanisms that involve fibres passing through the corpus callosum, and that may be unique to interhemispheric circuits 23 , 71 75 . Taken together, these features of PMv-to-M1 projections (the presence of both clear behavioural and clear physiological readouts, the link to a defined interhemispheric white matter tract) make them an ideal test bed for hypotheses about how myelin shapes circuit function and behaviour in humans.…”
Section: Introductionmentioning
confidence: 99%
“…While many anatomical tracing studies focus only on ipsilateral connections within a hemisphere, PMv has many transcallosal connections with heterotopic areas in the other hemisphere 67 , 68 and consistent with this anatomical observation it is established that PMv exerts similar facilitatory and inhibitory influences over the activity of M1 both ipsilaterally and contralaterally 45 , 46 , 66 , 69 , 70 . Therefore, the PMv-to-M1 circuit can also be studied interhemispherically, thus making it possible to probe mechanisms that involve fibres passing through the corpus callosum, and that may be unique to interhemispheric circuits 23 , 71 75 . Taken together, these features of PMv-to-M1 projections (the presence of both clear behavioural and clear physiological readouts, the link to a defined interhemispheric white matter tract) make them an ideal test bed for hypotheses about how myelin shapes circuit function and behaviour in humans.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that tract specificity can be lost through bottlenecks such as the corpus callosum when applying DTI-based tractography (117), although other studies have reported that deterministic tractography can achieve successful reconstruction of interhemispheric connections via the corpus callosum (118,119). In addition, interhemispheric connectivity via the corpus callosum that was reconstructed from conventional diffusion imaging data has been supported by high angular resolution diffusion imaging (HARDI), and also by post mortem examination of white matter anatomy (120)(121)(122).…”
Section: Discussionmentioning
confidence: 99%
“…84 This trade-off between inter-hemispheric and intra-hemispheric connectivity was also observed in a large-scale human study. 85…”
Section: Discussionmentioning
confidence: 99%
“…84 This trade-off between inter-hemispheric and intra-hemispheric connectivity was also observed in a large-scale human study. 85 Since maintaining a normal level of functional connectivity is essential for the brain to function properly, [86][87][88][89] we hypothesize that in birds, the evolution of brain connectivity took an alternative path in contrast with the emergence of corpus callosum in placental mammals; namely, that the left and right hemispheres developed stronger intra-hemispheric connectivity to compensate the lower inter-hemispheric connectivity while maintaining higher levels of hemispheric autonomy. This hypothesis is in agreement with higher telencephalic neuronal density, i.e.…”
Section: Functional Connectivity In Comparison With Human and Mammali...mentioning
confidence: 99%